ANALYSIS OF TEACHER CHALLENGES IN INCREASING MOTIVATION FOR LEARNING MATHEMATICS IN PRIMARY SCHOOL STUDENTS AT SDN KRATON 1 BANGKALAN - Firdausi Oktaviani; Mohammad Edy Nurtamam; Erna Dwi Lestari (STKIP Subang, 2024)
The aim of this research is to determine the challenges of teachers in increasing students' mathematics learning motivation at SDN Kraton 1. This research uses a qualitative approach with a case study type. Data was collected through several techniques, namely: Interviews, observation, and documentation. Based on research conducted by the author, a problem was found that students at SDN Kraton 1 lacked motivation in mathematics lessons. Students' negative perceptions of mathematics as a difficult subject, lack of family support in helping them study at home, and variations in students' basic abilities are the main obstacles in efforts to arouse students' interest in this subject. Even though schools have provided supporting facilities such as visual media and technology, their use is not optimal due to time constraints and high administrative demands.